Tingkat Kepuasan Petani Terhadap Benih Kentang Varietas Baru “X” Sebagai Bahan Baku Industri Pengolahan - Putra, Ivangga Dwi; Setiawan, Iwan; Suminartika, Eti (Universitas Galuh, 2024)
Imports of raw materials for the potato industry show fluctuations and an increasing trend. As local breeders are unable to provide the demand for industrial seed potatoes, about 4,000 tons of industrial seed potatoes are still imported by Indonesia every year, which is one of the reasons for the low domestic production of industrial potatoes. To meet demand, measures are needed to increase industrial seed potato production. A domestic university has been working to develop a new and improved industrial potato variety. Industrial potato variety